Analisis Stabilitas dan Simulasi Model Penyebaran Penyakit HIV/AIDS Tipe SIA (Susceptible, Infected, Abstained) - Zeth Arthur Leleury; Francis Yunito Rumlawang; Alva Grace Naraha (Department of Mathematics, Faculty of Mathematics and Natural Sciences, Pattimura University, Ambon, Indonesia, 2020)
HIV/AIDS is a disease that continues to grow and become a global problem that requires special attention. This can be seen from the high number of cases of HIV/AIDS every year. In this study, we discussed an analysis of stability of a point equilibrium and numerical simulation for the spread of HIV/AIDS. The mathematical models that we used is SIA (Susceptibles, Infected, Abstained) model. The model of SIA assumed that sub populations infected will increase because of the influence of the transmission rate sub populations infected to sub population susceptibles. However, mode of transmission of HIV is possible if the transmission of individual of sub populations abstained to individual of sub population susceptibles. The result of the model indicate that population growth rate is determined by theese parameters: birth, death, interaction and isolation. Based on the result of the model simulation showed that the impact of the sub populations abstained would affect so reduced sub population infected.